Association of Composite IS26-sul3 Elements with Highly Transmissible IncI1 Plasmids in Extended-Spectrum-β-Lactamase-Producing Escherichia coli Clones from Humans - Curiao, Tânia (American Society for Microbiology, 2011)
The association of an IS440-sul3 platform with Tn21 class 1 integrons carried by IncI1 plasmids encoding extended-spectrum β-lactamases (ESBLs; mainly SHV-12 and CTX-M-14) among worldwide Escherichia coli clones of phylogroups A (ST10, ST23, and ST46), B1 (ST155, ST351, and ST359), and D/B2 (ST131) is reported. An in silico comparative analysis of sul3 elements available in the GenBank database shows the evolution of sul3 platforms by hosting different transposable elements facilitating the potential genesis of IS26 composite transposons and further insertion element-mediated promoted arrangements.